COMBRETUM HEREROENSE SCHINZ (COMBRETACEAE): MEDICINAL USES, PHYTOCHEMISTRY, AND PHARMACOLOGICAL PROPERTIES - MAROYI, ALFRED (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Traditional knowledge about Combretum hereroense Schinz has been poorly documented, despite the ethnobotanical studies conducted in various parts of tropical Africa. Combretum hereroense is a small deciduous to semi-deciduous tree widely used in traditional medicine throughout its distributional range in tropical Africa. The present review compiles existing information on the medicinal, phytochemical and pharmacological properties of C. hereroense. A search for available information on the medicinal uses, phytochemical and pharmacological properties of C. hereroense was conducted by systematically searching the scientific databases such as ScienceDirect®, PubMed®, Web of Science, SpringerLink®, Google Scholar, Scopus® and SciELO, and as well as pre-electronic literature sources such as book chapters, books and other scientific publications obtained from the university library. This study showed that the bark, fruit, leaf, root, stem or shoot decoctions or infusions of C. hereroense are used as aphrodisiac, and traditional medicine against gastro-intestinal problems, infertility in women, respiratory infections, sexually transmitted infections, bilharzia, general body pains, headache, heart diseases, heartburn, malaria, sores and wounds. The phytochemical evaluation of the plant species revealed that it contains flavonoids, tannins, phenols, stilbenoids, phenanthrenes and triterpenoids. The pharmacological evaluations showed that the crude extracts and phytochemical compounds isolated from the species have anthelmintic, antibacterial, antimycobacterial, antifungal, anti-inflammatory and antioxidant activities. To realize the full potential of C. hereroense as traditional medicine, future studies should focus on conducting detailed phytochemical, pharmacological and toxicological evaluations, in vivo and clinical research.